Enhanced Oral Delivery of Asenapine Maleate from Solid Lipid Nanoparticles: Pharmacokinetic and Brain Distribution Evaluations (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: The aim of the present research work was to develop asenapine maleate (AM)-loaded solidlipid nanoparticles (AM-SLN) for the enhancement of oral bioavailability of drug and delivery to the brain.Materials and Methods: A 32 factorial design was used for the development and optimization of AM-SLN. Twoindependent variables, drug:lipid ratio (X1) and number of homogenization cycles (X2), were selected, whileparticle size and entrapment efficiency were selected as response variables. The optimized batch was evaluatedby various in vitro characterizations and in vivo pharmacokinetic and brain distribution studies. Results: Theparticle size, polydispersity index, entrapment efficiency, and zeta potential of optimized AM-SLN were found tobe 113 ± 4 nm, 0.34 ± 0.05, 72.4 ± 1.73%, and −41.4 ± 2.25 mV, respectively. Pharmacokinetic study indicatedsignificantly higher (P < 0.05) peak drug concentration (142.41 ± 8.14 ng/mL), area under the drug concentrationtimecurve (1561.81 ± 36.34 h ng/mL), and mean residence time (15.31 ± 3.21 h) of AM-SLN compared toAM-suspension (77.02 ± 5.74 ng/mL, 299.76 ± 39.42 ng/mL, and 2.73 ± 0.16 h, respectively) through oral route.Brain distribution study showed higher drug permeation across the blood–brain barriers and accumulation in thebrain. Conclusion: These findings demonstrate that SLNs could be a new promising drug delivery system for oraldelivery of AM in the treatment of schizophrenia.